How Do School Counselors Advocate for Gifted and Intelligent Children in Junior High School? - Findivia Egga Fahruni; Ach. Sudrajad Nurismawan; Nabila Salma Salsabila (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This case study research attempts to 1) investigate in detail the provision of advocacy services carried out by counseling guidance teachers to gifted and intelligent students in junior high school, 2) know the collaboration between counseling guidance teachers with homeroom teachers and parents in dealing with obstacles in gifted and intelligent students. Referring to the findings in schools, there are two forms of advocacy services provided by counselors: holding academic conferences and collaborating with homeroom teachers for gifted and intelligent children. Meanwhile, to handle the problems of gifted, intelligent children in terms of learning, social, and career, the counselor collaborates with subject teachers to provide enrichment materials and participate in the Olympics. Then, with parents, arrange social activities for gifted, intelligent children. At the same time, at home, and periodically provide group guidance related to career planning. The results of this study can be used as evaluation material for schools and become an inspiration, especially for policymakers in counseling guidance to facilitate the rights of gifted and intelligent children.